Curcumin Inhibits In Vitro SARS-CoV-2 Infection In Vero E6 Cells through Multiple Antiviral Mechanisms - Damariz Marín-Palma; Jorge H. Tabares-Guevara; María I. Zapata-Cardona; Lizdany Flórez-Álvarez; Lina M. Yepes; Maria T. Rugeles; Wildeman Zapata-Builes; Juan C. Hernandez; Natalia A. Taborda (Molecules, 2021)
Due to the scarcity of therapeutic approaches for COVID-19, we investigated the antiviral and anti-inflammatory properties of curcumin against SARS-CoV-2 using in vitro models. The cytotoxicity of curcumin was evaluated using MTT assay in Vero E6 cells. The antiviral activity of this compound against SARS-CoV-2 was evaluated using four treatment strategies (i. pre–post infection treatment, ii. co-treatment, iii. pre-infection, and iv. post-infection). The D614G strain and Delta variant of SARS-CoV-2 were used, and the viral titer was quantified by plaque assay. The anti-inflammatory effect was evaluated in peripheral blood mononuclear cells (PBMCs) using qPCR and ELISA. By pre–post infection treatment, Curcumin (10 µg/mL) exhibited antiviral effect of 99% and 99.8% against DG614 strain and Delta variant, respectively. Curcumin also inhibited D614G strain by pre-infection and post-infection treatment. In addition, curcumin showed a virucidal effect against D614G strain and Delta variant. Finally, the pro-inflammatory cytokines (IL-1β, IL-6, and IL-8) released by PBMCs triggered by SARS-CoV-2 were decreased after treatment with curcumin. Our results suggest that curcumin affects the SARS-CoV-2 replicative cycle and exhibits virucidal effect with a variant/strain independent antiviral effect and immune-modulatory properties. This is the first study that showed a combined (antiviral/anti-inflammatory) effect of curcumin during SARS-CoV-2 infection. However, additional studies are required to define its use as a treatment for the COVID-19.